2014
DOI: 10.1177/1534650114548311
|View full text |Cite
|
Sign up to set email alerts
|

Piloting A Family-Supported Approach to Concurrently Optimize Mental Health and Sport Performance in Athletes

Abstract: Participation in sports offers exceptional pro-social opportunities. However, sport participation also contributes to uniquely experienced stressors that may interfere with athletes' achievement in sports and mental health. In this study, we describe the initial process of empirically developing The Optimum Performance Program in Sports (TOPPS). We first review the need to adapt evidence-based behavioral interventions to optimize mental health in athletes. We then review the innovative features of TOPPS and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
(51 reference statements)
0
32
0
1
Order By: Relevance
“…Though beyond the scope of the present study, use of the APSQ alongside athlete-specific wellbeing interventions (e.g. Donohue et al, 2015Donohue et al, , 2018 may assist in determining the influence of scale domains on psychosocial and athletic functioning. If problems related to Self-Regulation and External Coping are associated with higher levels of psychological strain in athletes, it stands to reason that currently injured athletes would report higher scores on these factors, in addition to the athlete-specific Performance factor.…”
Section: Discussionmentioning
confidence: 99%
“…Though beyond the scope of the present study, use of the APSQ alongside athlete-specific wellbeing interventions (e.g. Donohue et al, 2015Donohue et al, , 2018 may assist in determining the influence of scale domains on psychosocial and athletic functioning. If problems related to Self-Regulation and External Coping are associated with higher levels of psychological strain in athletes, it stands to reason that currently injured athletes would report higher scores on these factors, in addition to the athlete-specific Performance factor.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of content, the program emphasized mental health awareness and sign-posting those with mental health problems to services, as opposed to providing coping strategies to alleviate mental health problems. To achieve improvements in well-being or resilience, a similar approach to previous programs that have reduced depressive symptoms and anxiety could be considered (Donohue et al, 2013;Donohue et al, 2015;Longshore & Sachs, 2015). For enhancement of the program, one session is likely not enough to achieve increased well-being or resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The Optimum Performance Program in Sports (TOPPS) is an evidence-based program that was adapted from Family Behavior Therapy (FBT; Azrin et al, 1994). In both uncontrolled and controlled case trials, TOPPS has preliminarily demonstrated concurrent improvements in mental health and sport performance in collegiate athletes (Chow et al, 2015; Donohue et al, 2015; Pitts et al, 2015), and outcomes are currently being examined in a large-scale randomized controlled trial in collegiate athletes (National Institute on Drug Abuse [NIDA]; 1 R01 DA031828).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%